Avaliação dos efeitos da acidificação e ressuspensão sobre a toxicidade do TBT em sedimentos marinhos - Antonioli, Roberta [UNIFESP] (2019)
TBT was the most widely used antifouling in the world between the 1960s and 2000s and due to its high toxicity, it was banned in 2003. However, as TBT persists in the sedimentary environment and its use is still observed in underdeveloped countries, several port and maritime areas around the world are still today heavily contaminated despite the regulations created. In addition to the inherent toxicity of TBT, physicochemical changes in the marine environment - such as acidification, and sediment resuspension (e.g. during dredging operations) - may alter the toxicity and bioavailability of TBT. Thus, the current study evaluated the effects of sediment acidification on TBT toxicity, as well as the influence of disturbance events associated with an acidified and contaminated marine environment. Toxicity of TBT-spiked whole sediment was evaluated by means of fecundity assay with Nitokra sp. Disturbance events were simulated by sediment elutriation and elutriate toxicity was assessed by embryo-larval development assays with Echinometra lucunter sea urchin embryos. The possible flow of the contaminant from sediment to water column in the absence of disturbance was evaluated by sediment-water interface (SWI) exposure with the same test used for the elutriate test. The results indicated that pH influences the toxicity of TBT in whole sediment to Nitokra sp. However, the concentration range tested was not suitable to identify the effect of pH or ressuspension on the toxicity of TBT, since no intermediate toxicity was found within the tested concentrations. The EC50-96h obtained for Nitokra sp was 372.5µg/kg (95% IC: 192.9 - 719.5µg/kg), however, in an acidified environment the value determined for EC50-96h was 4.2µg/kg (95% IC: 1.89 - 9.19µg/kg). For the elutriates and interfaces the values of EC50-42h did not differ significantly between them, nor in the different pHs tested. The EC50 values obtained in the present study indicate the need for further studies of quality guide values of sediments contaminated with TBT, considering that the environment is subject to resuspension events and physicochemical alterations. Values indicate the need for further studies that guide the quality guide values of TBT-contaminated sediments, especially when they are subject to resuspension events and physicochemical changes.